End of life: the responses of the Fuqaha' - Wan Muhammad, Ramizah (2016)
This paper is to discuss on the status of end of life according to the juristic views in Islamic jurisprudence. The author also discussed about the sanctity of life in Islam and the situations where life is permissible to be killed. Some legal maxims are highlighted in the context of end of life situations.